Analisis Tindak Tutur Direktif dalam Drama 3 Nen A Gumi Karya Komuro Naoko dan Suzuki - Pratama, Putu Diva Dian; Hermawan, Gede Satya; Yeni, Yeni (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 2 (2022)DO - 10.24843/JS.2022.v04.i02.p01, 2022)
The purpose of this research is to analyze the intent and types of directive speech act expressions in the drama 3 Nen A Gumi. The subject used in this research is a Japanese drama entitled 3 Nen A Gumi. This research is a qualitative descriptive research. The method used in this research is the listening method with an advanced technique, namely the note-taking technique. In analyzing, using pragmatic analysis to examine the use of intent and types of directive speech act expressions. The theory used is the theory of speech acts according to Searle (1979) and the theory of types of speech act expressions proposed by Nadar (2008). From the results of the research, it was found that 54 data were directive speech acts. There are 9 intents of directive speech acts found, namely request, entreat, question, invite, command, challenge, forbid, permit, and advise. Furthermore, it is known that directive speech acts are expressed by direct speech and indirect speech according to the context of the speech situation. There are 39 direct speech data and 15 indirect speech data.